2021
DOI: 10.3390/antiox10040568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preconception Selenium Intake on the Risk for Gestational Diabetes: The Japan Environment and Children’s Study

Abstract: Selenium (Se) acts as a cofactor of antioxidant enzymes. Preconception care may reduce the risk of gestational diabetes mellitus (GDM). We examined the association between preconception Se intake and the risk of GDM in Japanese women. Using the Japan Environment and Children’s Study database, we identified 92,764 Japanese women recruited between January 2011 and March 2014. Participants were categorized into five groups according to preconception Se intake quintiles (Q1 and Q5 were the lowest and highest Se in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The M0 data included gestational age at the time of GDM diagnosis. Japan's unique two‐step screening system conducted in the early and middle trimesters, allowed further categorization of GDM into early‐diagnosed (Ed‐, diagnosed <24 weeks) and late‐diagnosed (Ld‐, diagnosed ≧ 24 weeks) GDM 22,23 …”
Section: Methodsmentioning
confidence: 99%
“…The M0 data included gestational age at the time of GDM diagnosis. Japan's unique two‐step screening system conducted in the early and middle trimesters, allowed further categorization of GDM into early‐diagnosed (Ed‐, diagnosed <24 weeks) and late‐diagnosed (Ld‐, diagnosed ≧ 24 weeks) GDM 22,23 …”
Section: Methodsmentioning
confidence: 99%
“…This implies that PP, which affects placenta size, is associated with an increased risk of GDM. To the best of our knowledge, this is the first study that examined the association of PP with GDM (including Ed‐ and Ld‐GDM, which is unique to the Japanese GDM diagnosis system), 9,10 and we found that there was no correlation between PP and GDM.…”
Section: Discussionmentioning
confidence: 65%
“…In case of a positive screening result, a 75‐g OGTT is conducted with cut‐off values of ≥92 mg/dL for fasting plasma glucose, ≥180 mg/dL for plasma glucose at 1 h, and ≥ 153 mg/dL for plasma glucose at 2 h. GDM is confirmed if at least one of the three aforementioned glycemic levels is above the recommended threshold during the OGTT (fasting plasma glucose, plasma glucose at 1 h, and plasma glucose at 2 h). As Japan has a unique GDM screening system that is conducted during two pregnancy periods (the early‐ and mid‐trimesters), we further categorized GDM into early‐onset (Ed) GDM (diagnosed before 24 weeks) and late‐onset (Ld) GDM (diagnosed after 24 weeks) 9,10 …”
Section: Methodsmentioning
confidence: 99%
“…The effects of antioxidant supplementation on reproductive health are further explored in two original works in humans, in the context of pregnancy, included in our Special Issue [ 7 , 8 ]. These studies contribute to the still insufficient clinical evidence on the effects of antioxidant supplementation on human health.…”
mentioning
confidence: 99%
“…These studies contribute to the still insufficient clinical evidence on the effects of antioxidant supplementation on human health. In their work, Kyozuka et al retrospectively analyzed pre-conceptional selenium intake and the onset of gestational diabetes (GDM) in a large Japanese cohort [ 7 ]. Using multiple logistic regression, the authors estimated an increased risk for late-onset GDM in women with low pre-conceptional selenium intake, and an increased risk for the onset of GDM in women with very high selenium intake [ 7 ].…”
mentioning
confidence: 99%